1981
DOI: 10.1097/00004032-198105000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Corneal Epithelium to Krf Excimer Laser Pulses

Abstract: The response of the corneal epithelium of Dutch-belted rabbits to 50-nsec pulses of 248-nm KrF excimer laser radiation was studied with slit-lamp biomicroscopy. The corneal epithelium was examined at immediate, 1-, 2-and 24-hr postexposure times. At 24 hr, the observations were made with and without fluorescein staining. The damage endpoint (ED,,) was the 50% probability of detecting an opacity or fluorescein uptake. Damage EDso levels of 59 mJ/cm2 for 2-hr post-exposure and 3 mJ/cm2 for 24-hr postexposure (fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1986
1986
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 1 publication
0
12
0
1
Order By: Relevance
“…This goal is elusive because the tissues being ablated, particularly the epithe¬ lium and the stroma, are not homoge¬ neous tissues and therefore there will always be some irregularities in the ablated surface, as demonstrated dra¬ matically by the persistence of the epithelial cell nuclei and the irregu¬ larity of the corneal stromal surface that is seen at high magnification. To create a clinically useful instru¬ ment for photorefractive keratecto¬ my, six areas of knowledge must be refined: (1) Acceptable lasers with defined wavelengths and energy parameters must be identified.…”
Section: Morphologic Observationsmentioning
confidence: 99%
“…This goal is elusive because the tissues being ablated, particularly the epithe¬ lium and the stroma, are not homoge¬ neous tissues and therefore there will always be some irregularities in the ablated surface, as demonstrated dra¬ matically by the persistence of the epithelial cell nuclei and the irregu¬ larity of the corneal stromal surface that is seen at high magnification. To create a clinically useful instru¬ ment for photorefractive keratecto¬ my, six areas of knowledge must be refined: (1) Acceptable lasers with defined wavelengths and energy parameters must be identified.…”
Section: Morphologic Observationsmentioning
confidence: 99%
“…9 The reaction of the corneal tissue to UV radiation and the effect of UV radiation on other tissue may still have some potential for mutagenesis. [9][10][11][12][13] Chronic exposure to UV radiation between 315 nm and 400 nm can cause both nonmelanoma and melanoma skin cancers. 14 The risk for mutagenesis from 193 nm radiation is 1000 to 10 000 times less than the risk from 248 nm radiation, because 248 nm energy is absorbed predominantly by nucleic acids.…”
Section: Discussionmentioning
confidence: 99%
“…The transition of the popularity from incisional to ablative laser surgery arose with the development of EL technology [11]. In the early 1980s Taboada and Archiblad reported the use of EL to reshape the corneal epithelium [11,19] and Trokel et al demonstrated how EL could ablate bovine corneal stroma [11,20]. This last study demonstrated that EL with emission of 193 nm is ideal in terms of increasing the efficiency of ablation with no thermal damage to the surrounding collagen within the cornea [11].…”
Section: Historical Perspectivementioning
confidence: 99%